Efektifitas Buku Saku dalam Meningkatkan Pengetahuan Pendamping Ibu Nifas di Kabupaten Mamuju - Ahmady Ahmady; Agus Erwin Ashari (Jurnal Kesehatan Manarang, 2018)
Perinatal and neonatal period is a critical period for the baby's life. Two-thirds of infant deaths occur within 4 weeks after delivery and 60% of newborn deaths occur within 7 days after birth. Regular neonatal visits may early detect to prevent infant mortality. The family's role and support is enormous for the regularity of neonatal visits. The objective of the study was to know the effectiveness of the Pocket Book on the Knowledge of the Psychologist's Companion of the Babies' Period and the visit of the neonate. This research uses experimental Pre design. In this study, the subjects in the study consisted of two groups, the intervention group and the non-intervention group. The samples were the nearest relatives and lived in the same house with the mothers who delivered in housemother health service facilities from June to November 2017 in the work area of ​​the Binanga and Puskesmas Padang. The results showed that statistically significant results showed that there were differences in the average score of the puerperal and neonatal visits between the intervention group and the control group, thus the pocket book was effective for the improvement of maternal companion knowledge. Conclusion and Suggestion in this research that pocket book is effective for knowledge enhancement of maternal companion, and hopefully this pocket book need to be tested its validity by experts.